Stilizacija - Unuk, Drago (Revija za elementarno izobraževanje, 2013)
This conceptual paper provides a theoretical framework of stylisation as a phenomenon pertaining to stylistics. In verbal communication, style denotes a manifestation mode which results from ones deliberate choice of used and modified verbal and non-verbal elements. The style of a text is based on the selection of the means of expression, and results from the processes which intertwine within the text. We distinguish between stylistic differentiation and style-forming process. The more developed a language is, the vaster choice one has with regard to the use of linguistic features in stylisation. Gradual division of styles leads to the division of style elements: the function of a text determines the selection of means of expression and the division of styles. With regard to their stylistic markedness or emotional-expressive meaning, marked language elements are used in a precisely determined context, whereby the stylistic value is most notable in the vocabulary and syntactic elements used. Stylisation comprises the entire communication process which leads to the realisation of a specific style. There are several stylisation modes which normally intertwine as stylisation bundles, while style norm refers to managing the use of the style values of individual elements.
Keywords: jezikoslovna stilistika; stylistics; stil; style; stilemi; stylistically coloured word; stilizacija; stylisation; sopomenskost; synonymy; style norm; stylisation bundles